If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1x = 5x + 34 Reorder the terms: 5 + -1x = 34 + 5x Solving 5 + -1x = 34 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + -1x + -5x = 34 + 5x + -5x Combine like terms: -1x + -5x = -6x 5 + -6x = 34 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + -6x = 34 + 0 5 + -6x = 34 Add '-5' to each side of the equation. 5 + -5 + -6x = 34 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = 34 + -5 -6x = 34 + -5 Combine like terms: 34 + -5 = 29 -6x = 29 Divide each side by '-6'. x = -4.833333333 Simplifying x = -4.833333333
| -9+n=17 | | -26+x=x+23 | | 10-8x-7-2x=5 | | -4(z+2)+2z= | | -9*n=17 | | 0.7x-0.1(15-3x)=0.5(x-6) | | 3+4(2x-14)=-27 | | 1.5x=1.25x+8 | | y=400(13-x^2)(7x-8) | | 2x*2x+3y+3y+3y-x-x-x-x-y-y-y= | | x^2-4xy-21y^2= | | 8+7(7x-4)= | | 5-(x-7)+4x=7(x-1) | | 14-(3+3x)=x-9 | | 5y-7=0.6 | | -11x^3=704 | | -6(n-4)=40-4n | | 14(y-3)=10(5+y) | | 3(3x+4)-3=66 | | 3(3+4x)-3=66 | | x^2+37x+36= | | 7x-6x=70 | | 8x-(6x+6)=2 | | 10-(2x-5)=3(4x-2)-(5x-8) | | -3(x+1)+4x=10 | | x/3+26=25 | | 8x-(3x+4)=12 | | 3x^2-26x=-2x-7x-12 | | 4t-t-8=2t-4 | | 42=-5x+2 | | 6k+k+4=25 | | 4(6t+2)=80 |